The Partnership of Shadow Teachers with Elementary Students with Disabilities: An Islamic Education Perspective - Zulkipli Lessy; Yuli Kuswandari; Haresh Dalvi (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
Elementary students with disabilities faced intensified academic, social, and psychological barriers after the coronavirus pandemic. This study explores the approaches used by 12 shadow teachers in partnering with students with disabilities in 10 elementary schools in Yogyakarta, consisting of five urban and five rural schools. Using an exploratory qualitative design, data were collected through three rounds of in-depth interviews, a focus group discussion, and supporting observations and documentation. Participants were recruited voluntarily through a shadow teacher WhatsApp group and snowball referrals. Data were analyzed by repeatedly listening to digital recordings, checking them against verbatim transcripts, verifying field notes with a research assistant, and comparing participants' accounts to identify themes. The findings show that shadow teachers functioned as consultants, facilitators, motivators, and mediators who simplified course content, supported social competence, encouraged self-confidence, and negotiated barriers created by school policy, family poverty, stigma, and limited assessment. From an Islamic education perspective, inclusive schooling requires not only technical accommodation, but also ethical care, compassion, and affirmative recognition of students who are socially marginalized